2017
DOI: 10.1016/j.jclepro.2016.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Emergy analysis for the sustainable utilization of biosolids generated in a municipal wastewater treatment plant

Abstract: This contribution describes the application of an emergy-based methodology for comparing two management alternatives of biosolids produced in a wastewater treatment plant. The current management practice of using biosolids as soil fertilizers was evaluated and compared to another alternative, the recovery of energy from the biosolid gasification process. This emergy assessment and comparison approach identifies more sustainable processes which achieve economic and social benefits with a minimal environmental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…analysis framework [31]. The emergy approach has also compared two managem schemes for biosolids generated from wastewater treatment plants [32]. Impro evaluation indicators based on emergy analysis were created to compare the sustainab of different wastewater treatment processes [33] and evaluate the wastewater treatm system of a sugar mill in Kenya [34].…”
Section: Emergy Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…analysis framework [31]. The emergy approach has also compared two managem schemes for biosolids generated from wastewater treatment plants [32]. Impro evaluation indicators based on emergy analysis were created to compare the sustainab of different wastewater treatment processes [33] and evaluate the wastewater treatm system of a sugar mill in Kenya [34].…”
Section: Emergy Analysis Methodsmentioning
confidence: 99%
“…A wastewater treatment system of straw pulp papermaking and a wastewater treatment system of printing, dyeing, and papermaking were selected to evaluate the sustainability level of wastewater treatment systems in China, based on a hybrid neural network and emergy analysis framework [31]. The emergy approach has also compared two management schemes for biosolids generated from wastewater treatment plants [32]. Improved evaluation indicators based on emergy analysis were created to compare the sustainability of different wastewater treatment processes [33] and evaluate the wastewater treatment system of a sugar mill in Kenya [34].…”
Section: Introductionmentioning
confidence: 99%
“…It can then be used to compare different biosolid management alternatives. An emergy-based sustainability assessment of biosolids disposal options confirmed that gasification is energetically and environmentally suitable for biosolids disposal, and pre-processing of biosolids prior to their use in agriculture was shown to improve sustainability performance of this option (Cano Londoño et al 2017 ).…”
Section: Thermal Treatment and Resource Recoverymentioning
confidence: 99%
“…Taking the wastewater treatment in Happy Farmer's Home as an example, Junsheng et al confirmed several influencing factors on sustainability in China [35]. Natalia et al conducted an emergy assessment in a wastewater treatment plant, which compared two management alternatives of biosolids [36]. The wastewater treatment system from a sugar factory in Sweden was assessed on the basis of the emergy theory [37].…”
Section: Introductionmentioning
confidence: 99%